Pili torti and multiple facial milia as an expression of ectodermal dysplasia in monozygotic twins - Sikorska, Monika; Szczerkowska-Dobosz, Aneta; Purzycka-Bohdan, Dorota; Nowicki, Roman (Dermatology Review/Przegląd Dermatologiczny, 2014)
Introduction . Genodermatoses – congenital diseases with diverse clinical presentation – are caused by ectodermal defects. pili torti and milia may be features of these defects. Concomitantly these symptoms are present in rare genodermatoses: Bazex-Dupre-Christol syndrome and Jackson-Lawler syndrome. Objective. Presentation of monozygotic twins with identical hair structure disturbances typical for pili torti and multiple facial milia and review of syndromes and diseases with pili torti and/or milia, with particular reference to Bazex-Dupre-Christol syndrome. Case report . Three-year-old monozygotic twins with identical disturbances of the hair, which was dry, brittle, torn and showed in microscopic examination features typical for pili torti – twisting of the hair shaft by 180 ° . The scalp was overdried and scaly. Numerous milia on the face of both girls appeared at the age of 2 years and were noticed during the examination. The remaining structures derived from the ectoderm were normal. The patients were treated with adapalene cream applied once a day with partial improvement of follicular lesions on the face in both sisters. Conclusions . Coexistence of pili torti and multiple milia in twins indicates the genetic background of these disturbances. Due to potential risk of development of skin carcinoma in future, the patients require close follow-up.